Plasma concentrations of cathelicidin and β-defensins and their correlations in patients with basal cell carcinoma - Fijałkowska, Marta; Kowalski, Marek; Antoszewski, Bogusław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Non-melanoma skin cancers (NMSCs) are the most common neoplasms accounting for more than 95% of all of skin tumours and their incidence is dramatically increasing worldwide [1–3]. Skin cancers represent an important health problem and cause economic burden for the society and health services; it is said that NMSCs are about four times more costly than melanoma [4]. The pathogenesis of skin cancers is complex, however its exact mechanism of development has not been clearly described [3, 5]. There are some reports that paid attention to changes in the expression profile of specific proteins linked to skin carcinogenesis [6–9]. In this group there are b-defensins and cathelicidin, which are the key participles of innate host defence against microorganisms [6, 10]. The aim of this paper is to measure the plasma concentrations of b-defensins and cathelicidin in patients with basal cell carcinoma (BCC) in comparison to healthy controls (HC) and to check the significance of their correlations.